Are food insecure smallholder households making changes in their farming practices? Evidence from East Africa - Kristjanson, Patricia M.; Neufeldt, Henry; Gassner, Anja; Mango, Joash; Kyazze, Florence Birungi; Desta, S.; Sayula, George; Thiede, B.; Förch, Wiebke; Thornton, Philip K.; Coe, R. (Springer, 2012)
We explore the relationship between farming practice changes made by households coping with the huge demographic, economic, and ecological changes they have seen in the last 10 years and household food security. We examine whether households that have been introducing new practices, such as improved management of crops, soil, land, water, and livestock (e.g. cover crops, microcatchments, ridges, rotations, improved pastures, and trees) and new technologies (e.g. improved seeds, shorter-cycle and drought-tolerant varieties) are more likely to be food secure than less innovative farming households. Using data from a baseline household survey carried out in five sites and 700 households in four countries of East Africa (Kenya, Uganda, Tanzania and Ethiopia) across a range of agricultural systems and environments, this study contributes to the evidence base of what smallholders are doing to adapt to changing circumstances, including a changing climate. Lessons from both similarities and differences across sites are drawn. This unique baseline study provides a wide range of indicators of activities and behaviors that will be monitored over time. We found that many households are already adapting to changing circumstances, and their changes tend to be marginal rather than transformational in nature, with relatively little uptake of existing improved soil, water and land management practices. There is a strong negative relationship between the number of food deficit months and innovation, i.e. the least food secure households are making few farming practice changes. This has very different policy and investment implications depending on assumptions made as to the direction of causality.